A centenarian institutionalized patient who recovered from COVID-19 and developed immunity: a case study - Zambrano-Urbano, José Leonel; Buitrago-Gómez, Nathalia; Muñoz-Realpe, Juan Felipe; Ocampo-Chaparro, Jose Mauricio; Reyes-Ortiz, Carlos Alfonso (Universidad y Salud, 2021)
Introduction: SARS-CoV-2 virus, and the disease it causes (COVID-19), severely affects older adults (OA), especially those with multimorbidity and frailty. This is due to physiological mechanisms such as immunosenescence or poor control of inflammatory activity in this population. Studies of the diagnoses and treatments in these patients are scarce and many of them have low levels of evidence. Objective: To describe the clinical and paraclinical characteristics of a frail institutionalized centenarian female patient with multimorbidity who survived COVID-19 infection, developed immunity, and was treated in an acute geriatric unit. Case presentation: Institutionalized centenarian patient with multimorbidity and frailty who fulfilled the criteria for severe COVID-19 disease, was managed early, recovered, and eventually developed immunity. Conclusion: early diagnosis, early management and a comprehensive and interdisciplinary geriatric approach are essential for a favorable outcome in OA patients at high risk of COVID-19 disease progression.